Spatiotemporal evolution of venous narrowing in acute MS lesions. Issue 2 (March 2018) - Eisele, Philipp; Szabo, Kristina; Ebert, Anne; Brueck, Wolfgang; Platten, Michael; Gass, Achim
Abstract : Objective: To investigate the spatiotemporal evolution of venous narrowing in newly developing MS lesions in a longitudinal MRI study including susceptibility-weighted images (SWIs). Methods: We retrospectively investigated serial MR examinations of 18 patients with MS acquired on a 3T MRI system including SWI for acute contrast-enhancing lesions with at least 1 MRI examination before contrast enhancement. The mean diameter of veins at the time point of contrast enhancement was compared with the mean diameter of veins before and after contrast enhancement. Results: A total of 40 acute contrast-enhancing lesions with a corresponding intralesional central vein were included in the study. The mean diameter of intralesional veins at the time of contrast enhancement (0.80 ± 0.12 mm) was smaller than that at before (1.16 ± 0.19 mm) and after contrast enhancement (1.07 ± 0.15 mm; p < 0.001 for all comparisons). Conclusions: Our findings contribute to the increasing database of plaque development and evolution. The smaller diameter of intralesional veins on SWI at the time of blood-brain barrier breakdown may reflect morphologic changes because of perivascular inflammation and/or decreased levels of deoxygenated hemoglobin.